69.9k views
2 votes
Which is a solution of 3(x+4)-x=4

User Russ Lenth
by
4.7k points

2 Answers

4 votes

Hello.

The anser is: -4

Step 1: Simplify both sides of the equation.

3(x+4)−x=4

(3)(x)+(3)(4)+−x=4(Distribute)

3x+12+−x=4

(3x+−x)+(12)=4(Combine Like Terms)

2x+12=4

2x+12=4

Step 2: Subtract 12 from both sides.

2x+12−12=4−12

2x=−8

Step 3: Divide both sides by 2.

2x/2=−8/2

=-4

have a nide day

User Cameron Wilby
by
5.6k points
5 votes

Hey there

the answer is

3(x+4)−x=4

3(x+4)−x=4

(3)(x)+(3)(4)+−x=4

3x+12+−x=4

(3x+−x)+(12)=4

2x+12=4

2x+12−12=4−12

2x=−8

x=−4

thank you

best regards

OFFICIALLYSAVAGE2003

User Anvk
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.